Needs assessment and development of a freshman library orientation program for the Philippine Women's University with a survey of orientation programs of selected Metro Manila academic libraries - Borja, Clarita C. (1988)
The study is an attempt to 1) identify theories, concepts, and principles and describe current practice of library orientation programs (LOPs) in college and university libraries; 2) identify the information needs of PWU Freshmen students which should be provided through library orientation program; and 3) design and develop a library orientation program for the Philippine Women's University.